Bjorka: A Cyber Crime Phenomenon Which Gets Support from the Community Using Analysis of Criminological Perspective - Hegar Gagah Anantaka; Eva Achjani Zulfa; Surya Nita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Indonesia is experiencing several cybercrimes mostly in the form of online fraud and extortion, phishing and hacking. Since the Covid-19 pandemic hit, Indonesia has been faced with several hacking cases containing Indonesian people's personal data where this data was traded illegally on internet sites. One case that has received a lot of attention from the public in a longer period of time than usual is the hacking case by a hacker named Bjorka. However, the cyber crime case in the form of hacking and doxing that was carried out by Bjorka actually received support from the majority of Indonesian people rather than criticism. The criticism of the Indonesian people was actually directed at the government and this criticism was getting stronger driven by the hacktivism carried out by Bjorka. The research was compiled with the aim of knowing the background and factors that made the Bjorka cybercrime case different and popular among the public and thus gained support through a criminological perspective. The method used to compile this research is a qualitative method with literature study. This paper concludes that according to the RAT (Routine Activity Theory) Bjorka's cybercrime has succeeded in attracting the attention of the Indonesian people because Bjorka has the right motivation as an actor and target of victims, besides that government agencies are unable to maintain national cyber security with solidity. This study also has the conclusion that Bjorka received public support through his hacktivism on social media.